Pengaruh Spiritualitas Kerja terhadap Work Engagement pada Perawat - Hani Nurhaida Hafni; Muhammad Ilmi Hatta (UNISBA Press, 2022)
Abstract. In conditions of increasingly fierce economic competition nowadays, quality human resources are needed. Workplace spirituality can be a potential solution to create a conducive conditions for employees to work as well as possible. This study aims to determine how much influence workplace spirituality has on work engagement in nurses. There are two variables of this research. The first variable is workplace spirituality . The second variable is work engagement. The hypothesis in this study is that there is a positive influence of workplace spirituality on work engagement in employees. The subjects of this study were 85 nurses who active working and had 1 year minimum service period. The research data were obtained from the Workplace Spirituality Scale (WSS) from Milliman et al., (2003) which has been adapted into Indonesian by Widyarini (2011) and using the UWES-17 (Utrecht Work Engagement Scale) measuring instrument from Schaufeli, WB. , Salanova, M., Gonzalez-Roma, V., & Bakker (2002). The results of the study found that 100% of nurses had high workplace spirituality and 98.82% of nurses had high work engagement. The results of the influence of Workplace Spirituality on Work Engagement in this study amounted to 59.90%. The results of multiple regression show that the Meaningful Work (X1) dimension has an effect on Work Engagement. Abstrak. Dalam kondisi persaingan ekonomi yang semakin ketat seperti sekarang ini, diperlukan sumber daya manusia yang berkualitas. Spiritualitas kerja dapat menjadi solusi yang berpotensi dalam menciptakan keadaan yang kondusif bagi karyawan untuk bekerja sebaik mungkin. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh spiritualitas kerja terhadap work engagement pada perawat. Variabel penelitian ini adalah variabel satu yaitu spiritualitas kerja dan variabel dua yaitu work engagement. Hipotesis pada penelitian ini adalah terdapat pengaruh positif dari spiritualitas kerja terhadap work engagement pada karyawan. Subjek penelitian ini adalah 85 perawat yang aktif bekerja dan memiliki masa kerja minimal 1 tahun. Data penelitian diperoleh dari alat ukur Workplace Spirituality Scale (WSS) dari Milliman et al., (2003) yang telah diadaptasi ke dalam Bahasa Indonesia oleh Widyarini (2011) serta menggunakan alat ukur UWES-17 (Utrecht Work Engagement Scale) dari Schaufeli, W. B., Salanova, M., Gonzalez-Roma, V., & Bakker (2002). Hasil penelitian ditemukan 100% perawat memiliki Spiritualitas Kerja yang tinggi dan 98,82% perawat memiliki Work Engagement yang tinggi. Hasil pengaruh Spiritualitas Kerja terhadap Work Engagement pada penelitian ini sebesar 59,90%. Hasil multiple regression menunjukkan dimensi Meaningful Work (X1) memberikan pengaruh terhadap Work Engangement.